ANALISIS STABILITAS LERENG DENGAN MENGGUNAKAN METODE BIOTEKNIK PADA RUAS JALAN TAWAELI â€“ TOBOLI - Laela, Laela; Rahayu, Astri; Dwijaka, Agus (Jurusan Teknik Sipil Universitas Tadulako, 2014)
Tawaeli - Toboli is one of road that oftentimes undergo landslide. Most of these roads are in a mountainous area with steep slope angles . The road conditions worsened, especially the citizen do not know anywhere that is prone to landslides. The purpose of this study was to analyze slope stability using bioengineering methods. This method is used to increase the strength of the soil, and stabilize slopes and reduce erosion on slopes .The primary data for this study were obtained by conducting laboratory tests, including testing of bulk density, moisture content, density and shear testing directly without the influence of vegetation roots and the influence of vegetation roots to get the cohesion (c) and friction angle (Ï• ). Data field conditions include high slope and vegetation types. Analysis of slope stability calculated using the Slope / W. Calculation of earth pressure is calculated using the Rankine and Coulomb theories and calculations of stability against the collapse of the soil bearing capacity is calculated based on the equation Hansen and Vesic .From the results of the analysis showed that the presence of plant roots can increase the value of the cohesion and friction angle of the soil that can contribute to an increased safety factor of slope stability. Slope stability analysis using program Slope/W at the root of the condition without having the stability of the landslide is smaller compared with the conditions of using the roots , the results of the calculation of the shear strength of the soil without roots is smaller than the roots and results of calculations using the stability of the retaining wall retaining wall with the same dimensions at which point I Km 17 Â± 300, the cantilever type retaining walls with roots influences security ineligible dimensional slope stability due to the retaining wall is not in accordance with the conditions of soil containing the roots of plants. Increasing the value of cohesion and angle of friction on the ground with roots influences can maintain the stability of the slope. Keywords: retaining walls, bioengineering, landslide